Improvement in safety measures to reduce ED returns - Ghadah F Almugren; Mufareh Al Katheri; Ali M. al Khathaami; Abdul Hadi al-Qahtani; Abdulmohsen Al Saawi; Shiela Javellana; Mashael Basakran; Sara al yehya; Mohammed S Al Qarni (BMJ Open Quality)
Introduction Emergency department (ED) return cases as critical or deceased pose a significant concern for any healthcare organisation and need to be evaluated and addressed.Objectives A quality improvement initiative was implemented to reduce 50% of the return visits from the baseline proportion of return visits by critical/deceased adult patients to the ED within 72 hours of discharge during 1 year (January 2022–January 2023), which is a robust quality indicator. Additionally, factors that contribute to an admission or revisit within 72 hours of ED discharge were evaluated.Methodology The implementation of initiatives began in January 2022 to monitor the ED return cases. Interventions were developed using the plan–do–study–act cycles in January 2022. Cycle 1 captured ED returns within 72 hours that were flagged by daily systemic trigger notifications received through the email by the dashboard and the cases were analysed by our quality improvement specialists team daily in January 2022. In any sentinel or severe event, an escalation via SMS to the leadership ensured immediate attention and action. Cycle 2 included patient safety leadership meetings within 24 hours of the return visit. This was initiated in April 2022 and discussed with all stakeholders for the immediate implementation of recommendations and action plans to improve the system and address individual concerns. Cycle 3 included a comprehensive consultation checklist integrated into the HIS in July 2023 to ensure that all necessary steps and consultations were completed during discharge. This included specific questions regarding the consultant’s awareness about the treatment plan provided to the patient.Results A statistical process control chart was used to present the data through the dashboard from January 2021 to January 2023 and continued until December 2023. The results revealed significant improvements. Overall, the number of return patients in the ED reduced by 46.60% from 0.13% in 2021 to 0.08% in 2022 and 2023.Conclusion The project was highly effective for patients. It reduced the morbidity and mortality for these patients over time; however, it also increased immature admissions. Continuous monitoring and application of different measures to analyse ED return cases are recommended.